2013
DOI: 10.1186/1750-1172-8-143
|View full text |Cite
|
Sign up to set email alerts
|

Regional consensus opinion for the management of Beta thalassemia major in the Arabian Gulf area

Abstract: Thalassemia syndrome has diverse clinical presentations and a global spread that has far exceeded the classical Mediterranean basin where the mutations arose. The mutations that give rise to either alpha or beta thalassemia are numerous, resulting in a wide spectrum of clinical severity ranging from carrier state to life-threatening, inherited hemolytic anemia that requires regular blood transfusion. Beta thalassemia major constitutes a remarkable challenge to health care providers. The complications arising d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 87 publications
0
10
0
2
Order By: Relevance
“… Avoiding adverse reactions of blood transfusion therapy with appropriate red cell antigen typing, cross matching, and screening for new antibody production. 7 …”
Section: Transfusion Protocolmentioning
confidence: 99%
“… Avoiding adverse reactions of blood transfusion therapy with appropriate red cell antigen typing, cross matching, and screening for new antibody production. 7 …”
Section: Transfusion Protocolmentioning
confidence: 99%
“…28 The observed difference might be due to a difference in study participants. In the USA, the study was conducted on elderly patients with a mean age of 82 ± 9 which may be the cause of the higher incidence, but our study participant had median age 31 years old and reported with a few elder age groups (16,4.2%) whereas, in Nigeria, all participants were pregnant women (86% of the subjects were multigravid). Moreover, most of the transfusions administered were women who had an incomplete abortion and placenta previa with fetal-maternal hemorrhage which might be associated with ATR.…”
Section: Discussionmentioning
confidence: 92%
“…Blood component transfusion is an essential part of modern health care which can save lives and improve health. 1,2 The main goal of blood transfusion is to treat chronic anemia and ineffective erythropoietin, 3,4 coagulopathy, life-threatening bleeding diathesis. It is also used for the treatment of von Willebrand's disease, Hemophilia A, Factor XIII deficiency and hypofibrinogenemia, especially when recombinant products are not available.…”
Section: Introductionmentioning
confidence: 99%
“…A study by reported progressive renal failure to be one the main complications in βTM children. 20,21 Mishra 22,23 The use of iron chelation also affect functioning of glomeruli as DFO (Deferoxamine) given intravenously can also cause renal toxicity when given in high dose. However, DFO has decreased the rate of mortality by decreasing the cardiac and other complications.…”
Section: Resultsmentioning
confidence: 99%